Immunoinformatics approaches towards developing vaccine/therapeutic agent against the Middle East Respiratory Syndrome Coronavirus by targeting nsp3 protein - Tanvir, Niaj Mohammad (Brac University, 2020)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2019.